A comparison between fully-unsteady and quasi-steady approach for the prediction of the propeller performance in waves. (June 2020) - Saettone, Simone; Taskar, Bhushan; Regener, Pelle Bo; Steen, Sverre; Andersen, Poul
Abstract: Maritime transport is the most energy-effective mode to move large amounts of goods around the world. Hauling cargo via waterway produces an enormous quantity of greenhouse gas emissions. Vessel fuel efficiency directly influences ship emissions by affecting the amount of burnt fuel. Optimizing ships operating in waves rather than in calm water conditions could decrease the fuel consumption of vessels. In particular, ship propellers are traditionally designed neglecting dynamic conditions such as time-varying wake distribution and propulsion factors, propeller speed fluctuations, ship motions, and speed loss. The effect of waves on the propeller performance can be evaluated using both a quasi-steady and a fully-unsteady approach. The former is a fast computational approximation method based on the assumption that the ratio of propeller angular frequency to wave encounter frequency is sufficiently large. The latter provides a complete representation of the propeller dynamics, but it is computationally expensive. The purpose of this paper is to compare the propeller performance in the presence of waves using the quasi-steady and the fully unsteady approach. This analysis is performed by observing the differences in unsteady propeller forces, cavitation volume, and hull pressure pulses between the two approaches. The full-scale KVLCC2 propeller is utilized for the investigation. Results show a good agreement between the quasi-steady and the fully-unsteady approach in the prediction of the temporal mean and the fluctuation amplitude of KT and KQ, the cavity volume variation, and the hull pressure pulses. Therefore, for the considered operating conditions, the quasi-steady approach can be used to compute the propeller performance in waves.